2015
DOI: 10.1097/won.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Friction-Induced Skin Injuries—Are They Pressure Ulcers? An Updated NPUAP White Paper

Abstract: Friction injuries are often misdiagnosed as pressure ulcers. The reason for the misdiagnosis may be a misinterpretation of classic pressure ulcer literature that reported friction increased the susceptibility of the skin to pressure damage. This analysis assesses the classic literature that led to the inclusion of friction as a causative factor in the development of pressure ulcers in light of more recent research on the effects of shear. The analysis in this article suggests that friction can contribute to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…33,34 Authors of only one study 20 entered a shear-related variable into multivariate modeling; the study, which was of high quality, found that friction/shear (as defined by the Braden Scale) 35 was independently predictive of pressure injury development (Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…33,34 Authors of only one study 20 entered a shear-related variable into multivariate modeling; the study, which was of high quality, found that friction/shear (as defined by the Braden Scale) 35 was independently predictive of pressure injury development (Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…33 Principal causes of PU are pressure, friction and shear, and the resulting sustained cell and tissue deformations, the e ects of which are exacerbated by moisture and temperature (Fig 1). 1,[34][35][36][37][38][39][40][41]…”
Section: Data From Intensive Care Settingsmentioning
confidence: 99%
“…Tissue ischaemia, with or without reperfusion injury, and cellular deformation caused by mechanical loading are the commonly accepted aetiological factors for pressure ulcer development . Furthermore, lymphatic dysfunction caused by compression or ischaemia likely contributes towards pressure ulcer development.…”
Section: Pathophysiology Of Pressure Ulcer Developmentmentioning
confidence: 99%